Approximate analytic solutions of fractional Zakharov-Kuznetsov equations by fractional complex transform - Yulita, R.; Batiha, Belal; Shatnawi, "Mohd Taib" (International Journal of Applied Mathematical Research, 2016)
In this paper, fractional complex transform (FCT) with help of variational iteration method (VIM) is used to obtain numerical and analytical solutions for the fractional Zakharov-Kuznetsov equations. Fractional complex transform (FCT) is proposed to convert fractional Zakharov-Kuznetsov equations to its differential partner and then applied VIM to the new obtained equations. Several examples are given and the results are compared to exact solutions. The results reveal that the method is very effective and simple.